Effects of Elobixibat on Constipation and Lipid Metabolism in Patients With Moderate to End-Stage Chronic Kidney Disease - Matsuyama, Momoko; Hirai, Keiji; Nonaka, Hiroaki; Ueda, Moeka; Morino, Junki; Kaneko, Shohei; Minato, Saori; Mutsuyoshi, Yuko; Yanai, Katsunori; Ishii, Hiroki; Kitano, Taisuke; Aomatsu, Akinori; et al. (Frontiers in Medicine, 2022)
Objective: The aim of this study was to investigate the effects of elobixibat on constipation and lipid metabolism; and determine the factors associated with the effect of elobixibat on constipation in patients with moderate to end-stage chronic kidney disease (CKD). Methods: Stool frequency and serum lipid parameters were retrospectively analyzed before and after 4 weeks of elobixibat administration in 42 patients (CKD stage G3, 6; stage G4, 9; stage G5, 9; stage G5D, 18). Relationships between the change in stool frequency after initiation of elobixibat and various clinical parameters were analyzed by using linear regression analysis. Results: Elobixibat increased stool frequency from 0.5 ± 0.4 per day to 1.1 ± 0.6 per day (p<0.001) regardless of whether patients were undergoing dialysis, on concomitant laxatives, or were administered elobixibat before or after breakfast. Elobixibat reduced low-density lipoprotein cholesterol concentration (from 90.9 ± 37.2 mg/dL to 77.5 ± 34.8 mg/dL, p<0.05) and increased high-density lipoprotein cholesterol concentration (from 44.9 ± 14.3 mg/dL to 57.0 ± 25.8 mg/dL, p<0.05), but did not change triglyceride concentration. Adverse effects were observed in two patients (nausea and diarrhea). Only phosphate concentration was correlated with the change in stool frequency after initiation of elobixibat (standard coefficient = 0.321, p= 0.043). Conclusions: Elobixibat improved constipation and lipid metabolism in patients with moderate to end-stage CKD, without serious adverse events.